Measurement of the B-s(0) lifetime using semileptonic decays - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. -L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2006)
We report a measurement of the B-s(0) lifetime in the semileptonic decay channel B-s(0)-> D-s(-)mu(+)nu X (and its charge conjugate), using approximately 0.4 fb(-1) of data collected with the D0 detector during 2002-2004. Using 5176 reconstructed D-s(-)mu(+) signal events, we have measured the B-s(0) lifetime to be tau(B-s(0))=1.398 +/- 0.044(stat)(-0.025)(+0.028)(syst) ps. This is the most precise measurement of the B-s(0) lifetime to date.